Fishery livelihoods and an adaptation to climate change-induced threats at the Bhomra Wetland: a case study through a stakeholder-driven approach - Suman Kumari; Sanjeet Debnath; Uttam Kumar Sarkar; Lianthuamluaia Lianthuamluaia; Mishal Puthiyottil; Gunjan Karnatak; Basanta Kumar Das; Bandana Das Ghosh; Arijit Das (Journal of Water and Climate Change, 2023)
The main aim of the present study is to assess the present ecological status of Bhomra wetland with respect to the fisheries and associated ecosystem services and to prescribe some climate-smart adaptation technologies in changing climate. The analysis showed increasing temperature (Kendall's tau = 0.60, p<0.05) and decreasing rainfall (Kendall's tau = −0.33, p<0.05) in the studied region over the last two decades. The wetland is dominated by Cypriniformes species followed by Perciformes species. The overall production of the fish (i.e., 32155 kg) from the wetland in 2020 is below the average production of the last 10 year (i.e., 54704 kg). Canonical correspondence analysis reviled a strong correlation (p<0.05) between the fish assemblage and ecological parameters (mainly total alkalinity and available nitrate) of the wetland. Though the species diversity was moderate along with the moderate species richness (i.e., Shannon-Weiner diversity index = 1.581±0.007), the evenness (Simpson evenness index = 0.995±0.001) was high throughout the wetland. The wetland was found suitable for carp culture, but the ecosystem's health has degraded over time. The communication further suggests several climate-resilient strategies for sustainable utilization of wetland ecosystem services and increasing adaptive capacity of the fishers. HIGHLIGHTS The effect of climate change and anthropogenic stressors on a floodplain wetland ecosystem was assessed.; Historic climate data regarding temperature and precipitation were analysed.; The fish diversity of the selected wetland was measured using several diversity indices.; Both the stakeholders' perceptions and field-level vulnerability assessment were performed.; A sustainable plan on climate-smart adaptation strategies is proposed.;